Allogeneic hematopoietic stem cell transplantation from sibling and unrelated donors in pediatric patients with sickle cell disease—A single center experience. (24th October 2020) - Kogel, Friederike; Hakimeh, Dani; Sodani, Pietro; Lang, Peter; Kühl, Jörn‐Sven; Hundsdoerfer, Patrick; Künkele, Annette; Eggert, Angelika; Oevermann, Lena; Schulte, Johannes H.
Abstract: HSCT is curative in SCD. Patients with HLA‐identical sibling donor have an excellent outcome ranging from 90%‐100% overall and event‐free survival. However, due to the lack of matched sibling donors this option is out of reach for 70% of patients with SCD. The pool of potential donors needs to be extended. Transplantations from HLA‐matched unrelated donors were reported to be less successful with shorter event‐free survival and higher incidences of complications including graft‐vs‐host disease, especially in patients with advanced stage SCD. Here we report transplantation outcomes for 25 children with SCD transplanted using HLA‐matched grafts from related or unrelated donors. Overall survival was 100% with no severe (grade III‐IV) graft‐vs‐host disease and a 12% rejection rate. Mixed donor chimerisms only occurred in transplantations from siblings, while transplantations from unrelated donors resulted in either complete donor chimerism or rejection. Despite the small patient number, overall and disease‐free survival for unrelated donor transplantations is excellent in this cohort. The advanced disease state, higher alloreactive effect and stronger immunosuppression in unrelated donor transplantations raises patient risk, for which possible solutions could be found in optimization of transplant preparation, graft manipulation or haploidentical transplantation using T cell receptor α/β‐depleted grafts.